Light-Driven Crystal–Polymer Hybrid Actuators - Hasebe, Shodai; Matsuura, Daisuke; Mizukawa, Takaaki; Asahi, Toru; Koshima, Hideko (Frontiers in Robotics and AI, 2021)
Recently, soft robots, which are made of soft and light organic materials, have attracted much attention because of improved safety for daily interactions with humans. Mechanically responsive materials that can move macroscopically by external stimuli, such as light and heat, have been studied extensively over the past two decades, and they are expected to be applicable to soft robots. Among them, mechanically responsive crystals are attractive in terms of a larger Young’s modulus and faster response speed compared with polymers and gels. However, it is impractical to use one piece of a single crystal as a crystal machine; it is difficult to control the size of crystals and obtain large crystals. Hybridization of crystals with polymers is one way to create actuators with more realistic movements. Herein, we report a hybrid crystal assembly in which plate-like salicylideneaniline crystals are aligned in polymer films by a “rubbing” technique, a new approach which is inexpensive, easy, and applicable to a wide range of crystals and polymers. The hybrid films bent reversibly upon alternate irradiation with ultraviolet and visible light. The hybrid films bent as fast as single crystals, even when larger than single-crystal size, showing great mechanical performance originating from the advantages of both molecular crystals (fast response time) and polymers (large size). This work enriches the development of light-driven hybrid actuators composed of molecular crystals and polymers.